Branding of Kedungudi Sky Park Hill Ecotourism in the TikTok account @pesona_trawas - Utomo, Zulkifli Arizalu Satrio; Fikri, M. Andi (Universitas Muhammadiyah Sidoarjo, 2024)
Nature tourism (ecotourism) is a form of exploitation of natural resources that prioritizes the use of nature for human satisfaction. Indonesia has a very large area and has the potential for regional development if managed properly. Ecotourism is an option that can be used to advance the village by involving the full participation of the local community in every stage, from planning to supervision. Social media is any form of media that is present in a network with users who can interact, exchange ideas, and exchange content or what is often referred to as content. Social media can also be described as a guide to exchange quality information in the form of text, images, videos, and audio with users who use social media. The purpose of this study is to understand the role of the social media platform TikTok in increasing the number of visitors in Kedungudi Sky Park Hill. The theory used in this study is marketing communication, which serves as a guide for how the brand process takes place. This study uses a qualitative descriptive method. By taking data sources by purposive sampling using triangulation data collection techniques. The qualitative approach is a data collection method that produces descriptive data in the form of written or spoken words. Data sources were obtained from sources and other documents in the form of images and photos. The findings of this study show that the use of TikTok social media has succeeded in increasing the number of visitors at Kedungudi Sky Park Hill. By using the right visual content, it can attract the attention of the wider community.